The broken place - Shaara, Michael (Compass Rose Publishing, 2025)
Tom McClain returns home from the Korean War a wounded hero, seared by the intensity of brutal combat. Trying to reclaim his life as a medical student at a small New England college, he finds that the world he once knew no longer exists.McClain begins a relationship with a young college student who has fallen in love with him, but he is incapable of giving anything in return, consumed by memories he can't escape. A talented amateur boxer before the war, McClain turns professional, becoming a punishing fighter, knocking out each opponent he faces. As he nears the championship bout, he must fight a once great boxer on the way down. The outcome has profound consequences for both men.